Renovatio imperii Romani: The aspect of Christian wored outlook - Marius Ščavinskas (Lietuvos Istorijos Studijos)
There have not been any researches on the Medieval Christian world outlook done in Lithuania at all. A bit more attention was given to such problems as interaction of ancient Balts with Christian culture, Baltic view at Christianity. Usually, those topics are squeezed into the XIII-XIV century frame, which is more actual.